2013
DOI: 10.1007/s12011-013-9775-8
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoke Exposure During Pregnancy Increases Maternal Blood Lead Levels Affecting Neonate Birth Weight

Abstract: To assess the effect of lead exposure from cigarette smoke on fetal growth, blood lead concentrations were measured using inductively coupled plasma mass spectrometry in 150 healthy pregnant women. Mean lead concentrations in plasma and whole blood were significantly higher in the smoking group compared with the nonsmoking group in each trimester of pregnancy (p < 0.001). Logistic regression analysis showed the highest impact of the number of cigarettes smoked per day for serum lead concentration (β = 0.238; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 48 publications
2
28
0
4
Order By: Relevance
“…Bjermo et al (2013) have demonstrated meat intake to be inversely related to blood Cd concentrations. Smoking also contributes to increased blood Pb concentrations (Chelchowska et al, 2013;Taylor et al, 2013), and its uptake is found to be inversely related to Fe-stores (Mahaffey, 1990). Exposure of the general population to Pb has been linked to multiple sources including: dietary (e.g., consumption of foods grown on contaminated soils, some wines, hunted game and waterfowl and the associated use of leaded ammunition); leaded paints; contaminated soils and air; and certain hobbies such as making Pb sinkers Meltzer et al, 2013;Hanning et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Bjermo et al (2013) have demonstrated meat intake to be inversely related to blood Cd concentrations. Smoking also contributes to increased blood Pb concentrations (Chelchowska et al, 2013;Taylor et al, 2013), and its uptake is found to be inversely related to Fe-stores (Mahaffey, 1990). Exposure of the general population to Pb has been linked to multiple sources including: dietary (e.g., consumption of foods grown on contaminated soils, some wines, hunted game and waterfowl and the associated use of leaded ammunition); leaded paints; contaminated soils and air; and certain hobbies such as making Pb sinkers Meltzer et al, 2013;Hanning et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the maternal BLLs mean was 10.31µg/dl which was higher than that reported by other studies such as study done in Karachi by Hakeem A on pregnant women in 2003 where the mean of BLLs was 9.9 (14) , study done in New York in 2005 by Zhu M et.al where maternal BLLs mean was 2.1 (11) , other study done in Iraq (Mousil city) where the mean was 3.2 (22) and study done in Iran in 2005 where the mean of BLLs was 9.9 (15) .These differences between results of these studies may be due to the differences ingestational age at which blood samples have been taken and methods used for detection of BLLs including commercial kits, atomic absorption spectrometry and inductively coupled plasma mass spectroscopy. Nevertheless, the result of current study still reveals higher level in study sample.…”
Section: Discussion:-mentioning
confidence: 64%
“…The relationship between maternal blood lead levels and pregnancy out comes, includingmiscarriage, stillbirth, prematurity low birth weight andreduced head circumferences have had inconsistent results in studies (11)(12)(13)(14)(15)(16)(17) .Several studies were carried out in this concern,some of them found a significant association for example, study done by Xiex G in china 2013 (11) ,another done by Zhu M in New York 2008 (12) ,and study of ChelchowskaM,Ambroszkiewicz J in Poland 2013 (13) . Other studies found insignificant association such as study done by Hakeem A in Karachi 2003 (14) , Besharati A and Nasseri F in Islamic Republic of Iran 2005 (15) , study of MirghaniZ,Al-Rhashidi A in Saudi Arabia 2010 (16) , as well as study done by Rahman A in Kuwait 2012 (17) .…”
mentioning
confidence: 99%
“…Securing a cigarette smoke-free environment for children is of particular importance. The loss of the balance in gene expression resulting in a slight imbalance of the protein networks can result in developmental disorders in children [60][61][62][63] and ultimately in different disease patterns in adulthood [64][65][66][67] Our DAVID data show clearly, that negative regulators of transcription are down-regulated by tobacco smoke ingredients. A strongly decreased level of expression in the treated cells compared to the level of expression in their control cells suggests that gene products have tumor suppressor gene (TSG) function.…”
Section: Discussionmentioning
confidence: 77%